Pengaruh Kualitas Pelayanan terhadap Kepuasan Lansia di Poli Lansia UPTD Puskesmas Emparu Kabupaten Sintang - Leo, Donatus; Arifin, Arifin; Aripin, Sofjan (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
Health services at the poly elderly puskesmas need to be considered and the quality of service is still often questioned, especially at UPTD Puskesmas Emparu. This quantitative study aims to obtain information on the quality of service satisfaction of the elderly who visit the Puskesmas. This study involved 75 elderly (men 23 elderly, women 52 elderly) as research subjects. Data on service quality and satisfaction of the elderly were collected by filling out questionnaires. The collected data was analyzed using classical assumption tests, simple regression analysis, validity tests, reliability tests, and t (partial) tests with the help of SPSS application version 30. Information was obtained that the dimensions of direct evidence (tangibles) and responsiveness (responsiveness) affect elderly satisfaction with services in the elderly poly. The follow-up that needs to be done for the elderly at the UPTD Puskesmas Emparu elderly poly is to update facilities and infrastructure as needed and respond quickly in serving